Integrated Control of Grid-Forming and Grid-Following in Low-Inertia Environments - Yiizzan, Suffian; Ahmed Mohamed, Ahmed Haidar; Wan Azlan, Wan Zainal Abidin; Hazrul M., Basri (2024)
The growing integration of inverter-based resources (IBRs) such as solar photovoltaic (PV) systems and energy storage systems (ESS) is changing the dynamics of modern power grids. As renewable energy resources (RERs), such as solar PV systems, become more widespread, traditional power grids with mechanical inertia are being replaced, leading to significant challenges in maintaining grid stability due to reduced inertia. Despite various research on integrating microgrid technologies, there is still a lack of studies that look at the grid performance during a disturbance in a weak grid environment. To address such challenges, this paper proposes a hybrid technique that integrates grid-forming (GFM) and grid-following (GFL) inverter control within solar-powered microgrid systems in grid-connected and islanded modes. The proposed approach allows the inverter-based islanded microgrid to operate effectively without support from the utility grid. Thereby stabilizing frequency and voltage under disturbances even during low-inertia conditions. Simulation studies have been carried out to evaluate the capability of the integrated GFM and GFL in maintaining grid performance and enhancing the system during different conditions. The results highlight the potential of the hybrid GFM-GFL control system in reducing frequency deviations and voltage fluctuation.